A case-mix-adjusted comparison of early oncological outcomes of open and robotic prostatectomy performed by experienced high volume surgeons - Silberstein, Jonathan L. (2013)
OBJECTIVE: To compare early oncological outcomes of robot assisted laparoscopic prostatectomy (RALP) and open radical prostatectomy (ORP) performed by high volume surgeons in a contemporary cohort. METHODS: We reviewed patients who underwent radical prostatectomy for prostate cancer by high volume surgeons performing RALP or ORP. Biochemical recurrence (BCR) was defined as PSA ≥ 0.1 ng/mL or PSA ≥ 0.05 ng/mL with receipt of additional therapy. A Cox regression model was used to evaluate the association between surgical approach and BCR using a predictive model (nomogram) based on preoperative stage, grade, volume of disease and PSA. To explore the impact of differences between surgeons, multivariable analyses were repeated using surgeon in place of approach. RESULTS: Of 1454 patients included, 961 (66%) underwent ORP and 493 (34%) RALP and there were no important differences in cancer characteristics by group. Overall, 68% of patients met National Comprehensive Cancer Network (NCCN) criteria for intermediate or high risk disease and 9% had lymph node involvement. Positive margin rates were 15% for both open and robotic groups. In a multivariate model adjusting for preoperative risk there was no significant difference in BCR rates for RALP compared with ORP (hazard ratio 0.88; 95% CI 0.56–1.39; P = 0.6). The interaction term between nomogram risk and procedure type was not statistically significant. Using NCCN risk group as the covariate in a Cox model gave similar results (hazard ratio 0.74; 95% CI 0.47–1.17; P = 0.2). The interaction term between NCCN risk and procedure type was also non-significant. Differences in BCR rates between techniques (4.1% vs 3.3% adjusted risk at 2 years) were smaller than those between surgeons (2.5% to 4.8% adjusted risk at 2 years). CONCLUSION: In this relatively high risk cohort of patients undergoing radical prostatectomy we found no evidence to suggest that ORP resulted in better early oncological outcomes then RALP. Oncological outcome after radical prostatectomy may be driven more by surgeon factors than surgical approach.